Mad Tuscans and Their Families : A History of Mental Disorder in Early Modern Italy - Mellyn, Elizabeth Walker (Book collections on Project MUSE., 2014)
Drawing on the rich judicial archives of early modern Florence and its Tuscans domains, Mad Tuscans offers an innovative look at how families and courts of law worked together to forge pragmatic solutions to the range of problems madness introduced to their households.